Upaya Orang Tua Dalam Menanamkan Hablumminannas Pada Masa Covid-19 - Putri Ria Anggraini; Dewi Purnama Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to identify how parents' efforts to instill hablumminannas values in children during the Covid-19 period. This study uses a qualitative method. Information is obtained by the method of sowing questionnaires through the WhatsApp group and questions and answers to students, students and teachers. The results of this study prove that there is a fairly good progress in learning the personality and bonding of children and aged people throughout the upgrading from home. Personality values that can be raised from activities that students try at home are personality numbers (1) Religious, (2) Obedient, (3) Innovative, (4) Independent, (5) Responsibility, (6) Curiosity. . The conclusion of this research is that the growth of these personality values is the result of the synergy of teachers and aged people in guiding students with love, relationship, carrying out positive activities together in the Covid-19 pandemic.